Chad : Request for a Three-Year Arrangement Under the Extended Credit Facility and Cancellation of the Current Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Chad's Request for a Three-Year Arrangement under the Extended Credit Facility (ECF) and Cancellation of the Current Arrangement. The main elements of the program are the reestablishment of debt sustainability through external debt restructuring, achieving gradual fiscal adjustment by maintaining a tight spending envelope, better mobilizing non-oil revenue, and creating space for domestic arrears clearance. The aim is to stabilize the fiscal position and help achieve a durable economic recovery while supporting regional stabilization efforts. Strengthening public financial management and diversifying the economy are expected to support the efforts to strengthen the fiscal position and boost the non-oil sector. The IMF staff supports the authorities' request for a new ECF arrangement.